Pemberdayaan Masyarakat Berbasis Agribisnis Di Rumah Semai Hely Seedling And Farm Punggur, Lampung Tengah - Atika Riasari; Carmidah Carmidah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
Sectors that have an important role in the economy and meeting food needs, of course, must be followed by sustainable agricultural patterns to create agriculture that is resilient, advanced and efficient and has the competitiveness of farmers so that agribusiness-based empowerment efforts need to be carried out for the purpose of increasing the ability of farmers to empower vacant land.,the ability to provide organic fertilizers and plant seeds independently. The implementation of community service activities at the hely seedling nursery and farm punggur, Lampung is being carried out in several stages, namely the preparation stage, the implementation stage and the evaluation stage. The results of empowerment activities provide knowledge and understanding to partners on how to use vacant land into productive land so that it can be used as an alternative to increase economic welfare independently. This empowerment activity also improves farmers' skills in processing animal waste into organic fertilizer which can be processed and used as organic fertilizer.